Weimar modernism : philosophy, politics, and culture in Germany, 1918 - 1933 - Durst, David C. 1963- (Lexington Books, 2004)
Introduction: Weimar modernism -- Ernst Bloch's theory of nonsimultaneity -- Berlin Dada, Carl Schmitt, Georg Lukács, and the critique of contemplation -- From contemplation to distraction : the culture of inflation and the inflation of culture -- The art of disappearance : Adorno's aesthetics of modernism and Alban Berg's music -- From distraction to mobilization : Ernst Jünger, photography, and the imperial gaze of the worker -- From mobilization to interruption : dialectic at a standstill or Walter Benjamin on the politicization of the aesthetic in Brecht's epic theater